MDPV self-administration in female rats: influence of reinforcement history. - Doyle, Michelle R.; Sulima, Agnieszka; Rice, Kenner C.; Collins, Gregory T. (Psychopharmacology, 2021)
Rationale: A subset of male rats that self-administer 3,4-methylenedioxypyrovalerone (MDPV) have unusually high levels of drug intake; however, factor(s) that influence this behavior (e.g., reinforcement history and sex) are unknown. Objectives: Characterize the reinforcing potency and effectiveness of MDPV in female rats to determine whether (1) a subset of females also develop high levels of MDPV self-administration (i.e., a high-responder phenotype) and (2) the degree to which the high-responder phenotype is influenced by various reinforcement histories (i.e., responding for cocaine or food). Methods: Female Sprague Dawley rats initially responded for MDPV (0.032 mg/kg/infusion), cocaine (0.32 mg/kg/infusion), or food (45-mg grain pellet) under fixed ratio (FR) 1 and FR5 schedules of reinforcement. After 20 sessions, the cocaine- and food-history rats responded for MDPV for 20 additional sessions. Dose-response curves for MDPV were generated under FR5 and progressive ratio (PR) schedules of reinforcement. Results: A subset of rats responding for MDPV developed high levels of MDPV intake. A history of responding for cocaine, but not food, inhibited the development of high levels of MDPV intake. Large individual differences were observed in the level of self-administration when MDPV was available under an FR5, but not PR, schedule of reinforcement. Conclusions: MDPV functions as a powerful reinforcer in female rats, as has been previously reported in male rats. The substantial variability in MDPV self-administration between subjects may be related to individual differences in human drug-taking behavior.